Development of a Four-Tier Instrument of Acid-Base properties of salt Solution - Habiddin, Habiddin; Ameliana, Devita Novi; Su’aidy, Muhammad (JCER (Journal of Chemistry Education Research), 2020)
Many chemistry teachers claimed that identifying students' understanding genuinely is challenging due to the limited time available, and the overload works faced. Therefore, constructing an efficient and valid instrument to overcome this difficulty is a must. This study is a part of the big project to produce a robust four-tier instrument to identify students' conception of acid-base properties of salt solution (FTI-ABPS2). The project involved six groups of researchers, and each group carried out the study in 6 different participant groups and schools. This paper outlines the development and validation of a four-tier instrument of Acid-Base properties of salt Solution involving public secondary school students in Malang Regency. The instrument was constructed using the procedure as carried out by Habiddin & Page (2019). Twenty-eight questions were constructed for the instrument. The results show that the instrument is valid and reliable to be implemented further. In-depth analysis regarding content validity, as well as the empirical validity of the instrument in light with the characteristic of chemical concepts (acid-base properties of salt solution in particular), is also discussed.